Humorous Learning. Dialogical Uses of Humor in Training Situations - Bos, Jaap; Zomer, Peter (Studia Psychologica: Theoria et praxis, 2008)
This article explores an activity observed predominantly in training situations: humorous encounters that imply some form of learning. Humorous learning is a specific form of engagement in which contradicting or opposing voices are incorporated into the systm of I-positions of the actor through the use of humour. This technique is presented here as a collective contradiction solving mode that allows the student to learn to reposition himself in the field. The article discusses data from a case study in which a training session involving multiple trainees and three trainers was evaluated. The sessions were tape-recorded and transcribed; a discursive analysis of two transcripts is presented and discussed. What makes humorous learning singular is that it allows participants to distance themselves from an immediate situation while it simultaneously creates a window of opportunity in which new, unforeseen possibilities arise.